A Decade of Spectacular Progress for M.I.T., Manipal-The First Self Financed Engineering College in India - Prabhakar, Alladi (Journal of Engineering Education Transformations, 1993)
When one talks about the progress and development of a self financing institution, one has naturally to recount the life and work of Dr. T. M. A. Pai, the great visionary, educationist, and doctor, who was responsible for Â·the starting of several Educational Institutions in the district of South Canara.